Association of dietary patterns with hypertension among adults residing in Tibetan China: findings from a population-based study - Li, Xinran; Zhang, Xin; Gou, Qiling; Meng, Qingtao; Chen, Xiaoping (Frontiers in Nutrition, 2025)
ObjectivesThis study aimed to investigate the dietary patterns of Tibetan residents and explore their association with the prevalence of hypertension.MethodsA multi-stage, stratified, random sampling method was employed to include Tibetan residents from Luhuo County, Garze Tibetan Autonomous Prefecture, Sichuan Province, China. Dietary information was collected through face-to-face interviews using a Food Frequency Questionnaire (FFQ) consisting of 92 food items. Participants were asked to report the frequency and portion size of their consumption of each food item over the past year. The collected data were subsequently converted into average daily intake, with the 92 food items grouped into 23 distinct categories. Principal Component Analysis (PCA) was then used to identify dietary patterns. Binary logistic regression analysis was conducted to investigate the association between dietary patterns and the prevalence of hypertension, adjusting for potential confounders including age, gender, living area, education, physical activity, current smoking, current alcohol consumption, diabetes, dyslipidemia, and overweight/obesity. A P value <0.05 was considered statistically significant.ResultsA total of 1,262 Tibetan residents participated in the study, with an average age of 46 ± 15 years. Among them, 36.8% were male, and the prevalence of hypertension was 30.2%. Three distinct dietary patterns were identified among Tibetan residents and were subsequently named as the “Tsamba-red meat-tuber,” “Rice-vegetable-fruit,” and “Dairy products” patterns. After adjusting for confounding factors, individuals in the highest quartile following the “Tsamba-red meat-tuber” pattern were found to be associated with a higher prevalence of hypertension (OR = 3.04, 95% CI: 2.06–4.50; P for trend <0.001). In contrast, individuals in the highest quartile following the “Rice-vegetable-fruit” pattern were associated with a lower prevalence of hypertension (OR = 0.45, 95% CI: 0.30–0.67; P for trend <0.001). Additionally, those in the highest quartile of the “Dairy products” pattern also showed a lower prevalence of hypertension (OR = 0.58, 95% CI: 0.39–0.85; P for trend = 0.002).ConclusionThe “Tsamba-red meat-tuber” pattern is associated with a higher risk of hypertension, whereas the “Rice-vegetable-fruit” and “Dairy products” patterns are associated with a lower risk of hypertension in this population.